Non-Equilibrium Li Insertion Paths in LiMn0.75Fe0.25PO4 Observed during the Relaxation Process. (10th January 2015) - Satou, Yoshinori; Komine, Shigeki; Takai, Shigeomi; Yao, Takeshi
Abstract : We observed in detail the XRD profiles of LiMn0.75 Fe0.25 PO4 taken during the relaxation time. We founded the peak position of the Li-rich phase shifted to lower angles during the relaxation process. We also founded that the intensity around the midpoint between the peak positions of the Li-rich phase and that of the Li-lean phase decreased immediately after the lithium insertion and the delay of the decrease in the intensity around the Li-rich phase. We consider that these happened due to the crystal structure peculiar to the lithium manganese iron phosphate.